2019
DOI: 10.1126/sciadv.aax3894
|View full text |Cite
|
Sign up to set email alerts
|

High density of genuine growth twins in electrodeposited aluminum

Abstract: We demonstrate the synthesis of highly twinned Al using electrodeposition and propose a model for the continuous twin nucleation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 52 publications
1
10
1
Order By: Relevance
“…We found that the twinned NC Al sample has a higher strength than the non-twinned NC Al sample as it has a higher yield point. These results are consistent with the higher hardness measured experimentally (more than 900 MPa for twinned Al and 600 MPa for non-twinned Al) [23]. Furthermore, although in the later stage of shear deformation the stress between non-twinned and twinned NC Al sample became comparable, twinned sample showed an obviously larger stress in the earlier stage of deformation.…”
Section: Uniform Shearsupporting
confidence: 91%
“…We found that the twinned NC Al sample has a higher strength than the non-twinned NC Al sample as it has a higher yield point. These results are consistent with the higher hardness measured experimentally (more than 900 MPa for twinned Al and 600 MPa for non-twinned Al) [23]. Furthermore, although in the later stage of shear deformation the stress between non-twinned and twinned NC Al sample became comparable, twinned sample showed an obviously larger stress in the earlier stage of deformation.…”
Section: Uniform Shearsupporting
confidence: 91%
“…In the present case of laser ablation, both twin formation processes can take place since growth under non-equilibrium conditions or thermal stresses on particles that are expected to occur, favor twin formation. 77,78 One can assume that by increasing F the rate of thermal stresses on crystalline structures increases and nanoparticles with different phases containing various crystallographic defects can be formed as a result of formation of a supercritical temperature liquid, high pressure-temperature cavitation bubble and post-irradiation of already synthesized nanoparticles.…”
Section: Analysis Of Nanoparticlesmentioning
confidence: 99%
“…Compared to the aforementioned Al deposits obtained from AlCl 3 –[EMIm]Cl ILs, , the nanohardness of Al deposits has been significantly improved for the concentrated AlCl 3 –G2 electrolyte. In addition, as for the bulk Al with a crystallite size of 1.2–1.5 μm produced through severe plastic deformation, the nanohardness and elastic modulus are approximately 0.85 and 72 GPa, respectively .…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, both the nanohardness and elastic modulus are available from the nanoindentation tests. For instance, in the AlCl 3 –1-ethyl-3-methylimidazolium chloride ([EMIm]­Cl) IL baths, the Al deposits with a crystallite size of 1 and 2 μm have been obtained. , They correspond to a nanohardness of 0.9 and 0.71 GPa, respectively. Meanwhile, the corresponding elastic modulus is 65.2 and 44.9 GPa, respectively.…”
Section: Resultsmentioning
confidence: 99%